Identification of the Primary Lesion of Toxic Aluminum in Plant Roots . Issue 4 (10th February 2015) - Kopittke, Peter M.; Moore, Katie L.; Lombi, Enzo; Gianoncelli, Alessandra; Ferguson, Brett J.; Blamey, F. Pax C.; Menzies, Neal W.; Nicholson, Timothy M.; McKenna, Brigid A.; Wang, Peng; Gresshoff, Peter M.; Kourousias, George; et al.
Abstract : The primary mechanism of aluminum toxicity was found to be apoplastic, with aluminum binding to the cell wall inhibiting loosening required for root elongation. Abstract: Despite the rhizotoxicity of aluminum (Al ) being identified over 100 years ago, there is still no consensus regarding the mechanisms whereby root elongation rate is initially reduced in the approximately 40% of arable soils worldwide that are acidic. We used high-resolution kinematic analyses, molecular biology, rheology, and advanced imaging techniques to examine soybean ( Glycine max ) roots exposed to Al . Using this multidisciplinary approach, we have conclusively shown that the primary lesion of Al is apoplastic. In particular, it was found that 75 µm  Al reduced root growth after only 5 min (or 30 min at 30 µm  Al ), with Al being toxic by binding to the walls of outer cells, which directly inhibited their loosening in the elongation zone. An alteration in the biosynthesis and distribution of ethylene and auxin was a second, slower effect, causing both a transient decrease in the rate of cell elongation after 1.5 h but also a longer term gradual reduction in the length of the elongation zone. These findings show the importance of focusing on traits related to cell wall composition as well as mechanisms involved in wall loosening to overcome the deleterious effects of soluble Al .